Consensus or Contestation? The Memory of Saint Louis During the Restoration, 1814–30. (10th April 2019) - Heath, Sean
Abstract: Did the revival of pre-Revolutionary royal culture that accompanied the Restoration help to create consensus around the monarchy or did it fuel contestation in the fractured political landscape of the period? An important case study is Saint Louis, whose memory was used by the monarchy to bolster its legitimacy and on whose feast day royalists celebrated their loyalty to the crown. However, his most ardent admirers' refusal to allow his memory to serve anything other than an ultra-royalist and Catholic position ensured that he never became a symbol of wider consensus and reconciliation. As such, this article argues that the revival of his memory in this period is revealing of an important characteristic of monarchical culture during the Restoration, namely that its success in consolidating partisan support among royalists and Catholic traditionalists was inversely related to its ability to secure broader and more lasting political consensus.